Association of the TNFAIP3 rs5029939 variant with systemic sclerosis in the European Caucasian population. Issue 11 (28th May 2010) - Dieudé, P; Guedj, M; Wipff, J; Ruiz, B; Riemekasten, G; Matucci-Cerinic, M; Melchers, I; Hachulla, E; Airo, P; Diot, E; Hunzelmann, N; Cabane, J; et al.
Abstract : Background: TNFAIP3 encodes the ubiquitin-modifying enzyme, a key regulator of inflammatory signalling pathways. Convincing associations between TNFAIP3 variants and autoimmune diseases have been reported. Objective: To investigate the association of TNFAIP3 polymorphisms with systemic sclerosis (SSc). Methods: Three single nucleotide polymorphisms (SNPs) in a set of 1018 patients with SSc and 1012 controls of French Caucasian origin were genotyped. Two intergenic SNPs, rs10499194 and rs6920220, and one located in TNFAIP3 intron 2, rs5029939, were selected. The TNFAIP3 rs5029939 found to be associated with SSc in this first set was then genotyped in a second set of 465 patients with SSc and 182 controls from Germany and 184 patients with SSc and 124 controls from Italy. Pooled odd ratios were calculated by Mantel–Haenszel meta-analysis. Results: The rs5029939 G allele was found to be significantly associated with SSc susceptibility (pooled OR=2.08 (95% CI 1.59 to 2.72); p=1.16×10 −7 ), whereas the rs10499194 and rs6920220 variants displayed no association. Only one of the predicted haplotypes investigated in the French sample was significantly associated with SSc (p=8.91×10 −8 ), and this haplotype was discriminating only in the presence of the rs5029939 risk allele, suggesting that this SNP tags the association signal. The strongest associations of rs5029939 with subphenotypes, having large magnitudes for complex genetic disorders, were observed for diffuse cutaneous SSc (pooled OR=2.71 (1.94 to 3.79), p=5.2×10 −9 ), fibrosing alveolitis (pooled OR=2.26 (1.61 to 3.17), p=2.5×10 −6 ) and pulmonary arterial hypertension (pooled OR=3.11 (1.86 to 5.17), p=1.3×10 −5 ). Conclusion: These results suggest that TNFAIP3 is a genetic susceptibility factor for SSc.